Encapsulation into Stealth Liposomes Enhances the Antitumor Action of Recombinant Cratylia mollis Lectin Expressed in Escherichia coli - Cunha, Cássia R. A. da; Silva, Luís C. N. da; Almeida, Fábio J. F.; Ferraz, Milena S.; Varejão, Nathalia; Cartaxo, Marina F. de Souza; Miranda, Rita de Cássia M. de; Aguiar, Francisco C. A. de; Santos, Noemia P. da Silva; Coelho, Luana C. B. B.; Santos-Magalhães, Nereide S.; Correia, Maria T. dos Santos (Frontiers in Microbiology, 2016)
This study evaluated the in vivo antitumor potential of the recombinant lectin from seeds of Cratylia mollis (rCramoll) expressed in Escherichia coli, free or encapsulated in stealth liposomes, using mice transplanted with sarcoma 180. rCramoll-loaded stealth liposomes (rCramoll-lipo) were formulated by hydration of the lipid film followed by cycles of freezing and thawing, and about 60% of rCramoll was encapsulated. This novel preparation showed particle size, polydispersity index, and pH suitable for the evaluation of antitumor activity in vivo. Tumor growth inhibition rates were 59% for rCramoll and 75% for rCramoll-lipo. Histopathological analysis of the experimental groups showed that both free and encapsulated lectin caused no changes in the kidneys of animals. Hematological analysis revealed that treatment with rCramoll-lipo significantly increased leukocyte concentration when compared with the untreated and rCramoll group. In conclusion, the encapsulation of rCramoll in stealth liposomes improves its antitumor activity without substantial toxicity; this approach was more successful than the previous results reported for pCramoll loaded into conventional liposomes. At this point, a crucial difference between the antitumor action of free and encapsulated rCramoll was found along with their effects on immune cells. Further investigations are required to elucidate the mechanism(s) of the antitumor effect induced by rCramoll.